Adhesive tape and wire harness including the same

The adhesive tape with an olefin resin base, undercoat, and acrylic adhesive layer addresses telescoping and stickiness issues, ensuring robust adhesive strength for wire harness applications.

JP2024176840AInactive Publication Date: 2024-12-19YAZAKI CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023095665
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional halogen-free tapes used in wire harnesses face issues with telescoping and stickiness due to lubricant blooming, leading to reduced adhesive force and difficulty in maintaining adhesive strength.

Method used

An adhesive tape design featuring a base material made of olefin resin, an undercoat layer, and an adhesive layer with specific thickness and composition, eliminating the need for lubricants and ensuring optimal adhesive strength and preventing telescoping and stickiness.

Benefits of technology

The adhesive tape effectively suppresses telescoping and stickiness while maintaining excellent adhesive strength, suitable for use in wire harnesses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176840000001_ABST
    Figure 2024176840000001_ABST
Patent Text Reader

Abstract

To provide an adhesive tape that prevents the occurrence of the telescoping phenomenon and stickiness on the tape side while exhibiting superior adhesive strength, and a wire harness including the same.SOLUTION: An adhesive tape 1 comprises: a substrate 2 containing olefin resin; a primer layer 3 disposed on one side of the substrate 2; and an adhesive layer 4 disposed on the surface of the primer layer 3 opposite the substrate 2, containing acrylic resin, and having a thickness of 5 μm or more and 20 μm or less. The self-back adhesive strength is 1.0 N / 10 mm or more and 3.0 N / 10 mm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape and a wire harness using the same. [Background technology]

[0002] In consideration of environmental conservation, halogen-free tapes are being used in place of polyvinyl chloride tapes for bundling and protecting electric wires in wire harnesses. Conventional halogen-free tapes use olefin resins, with an emphasis on heat resistance and flexibility.

[0003] In the substrate processing method for halogen-free tapes, calendar processing has been widely adopted because it can increase production volume. This processing adds a lubricant to the substrate, which prevents the sheeted film from sticking to the roll during production and increases the precision of the substrate thickness. Patent Document 1 discloses an adhesive tape with a polyolefin substrate containing a lubricant. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-194061 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in Patent Document 1, the lubricant blooms on the substrate surface, reducing adhesive strength, so it is necessary to thicken the adhesive layer to prevent edge peeling and ensure adhesive strength. On the other hand, thickening the adhesive layer increases the likelihood of the adhesive tape experiencing a telescoping phenomenon (where the center of the wound tape rises and deforms into a bowl shape), and there is also the problem that the sides of the tape tend to become sticky.

[0006] The present invention has been made in view of the problems inherent in the conventional techniques, and an object of the present invention is to provide an adhesive tape which is excellent in adhesive strength and which suppresses the occurrence of the telescope phenomenon and stickiness on the side surfaces of the tape, and a wire harness using the same. [Means for solving the problem]

[0007] The adhesive tape according to one embodiment of the present invention comprises a substrate containing an olefin resin, an undercoat layer disposed on one side of the substrate, and an adhesive layer disposed on the side of the undercoat layer opposite the substrate, the adhesive layer containing an acrylic resin and having a thickness of 5 μm or more and 20 μm or less, and has an adhesive strength to its back surface of 1.0 N / 10 mm or more and 3.0 N / 10 mm or less.

[0008] A wire harness according to another aspect of the present invention includes an adhesive tape. Effect of the Invention

[0009] According to the present invention, it is possible to provide an adhesive tape which suppresses the occurrence of the telescope phenomenon and stickiness on the side surfaces of the tape and has excellent adhesive strength, and a wire harness using the same. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing an adhesive tape according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the pressure-sensitive adhesive tape according to the present embodiment will be described in detail with reference to the drawings. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios.

[0012] The adhesive tape 1 of this embodiment comprises a substrate 2 containing an olefin resin, an undercoat layer 3 disposed on one side of the substrate 2, and an adhesive layer 4 disposed on the side of the undercoat layer 3 opposite the substrate 2.

[0013] [Base material] The substrate 2 contains an olefin resin. The olefin resin is not particularly limited, but at least one selected from the group consisting of low-density polyethylene, linear polyethylene, medium-density polyethylene, high-density polyethylene, very low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolypropylene, polybutene, and polymethylpentene can be used. From the viewpoints of flexibility and heat resistance, the olefin resin is preferably a propylene-based resin (homocopolymer or copolymer) containing propylene as a monomer, and in particular, a propylene-ethylene copolymer is preferable.

[0014] The thickness of the substrate 2 is not particularly limited, but is preferably 30 μm to 200 μm, and more preferably 60 μm to 120 μm. By making the thickness of the substrate 2 30 μm or more, the tensile strength of the pressure-sensitive adhesive tape 1 can be improved. Furthermore, by making the thickness of the substrate 2 200 μm or less, the occurrence of wrinkles that occur when the pressure-sensitive adhesive tape 1 is wrapped around an electric wire or the like can be suppressed.

[0015] In addition to the olefin resin, various additives may be blended in appropriate amounts to the extent that the effects of the present embodiment are not impaired in the base material 2. Examples of additives that may be added include talc, softeners, antioxidants, antistatic agents, antiblocking agents, antiaging agents, copper damage inhibitors, and flame retardants.

[0016] The method for forming the substrate 2 is not particularly limited, but for example, the substrate 2 can be formed by a method in which a resin extruded from a T-die is stretched to form a sheet. The substrate 2 may be any of an unstretched film, a uniaxially stretched film, a biaxially stretched film, etc., but is preferably a biaxially stretched film stretched both lengthwise and widthwise from the viewpoint of strength.

[0017] In conventional calendar processing, it was necessary to add a lubricant to the substrate to prevent the sheeted film from sticking to the heat roll during production. However, since the substrate 2 can be formed by T-die processing and is a cooling roll, it is not necessary to add a lubricant to the substrate 2. Therefore, there is no decrease in adhesive strength due to the lubricant blooming on the surface of the substrate 2, and it is possible to reduce the thickness of the adhesive layer 4 described below.

[0018] [Undercoat layer] The undercoat layer 3 is disposed on one surface of the substrate 2. In this embodiment, by disposing the undercoat layer 3 on one surface of the substrate 2, it is possible to prevent the components of the adhesive layer 4 from migrating to the substrate 2 and suppress discoloration of the adhesive tape 1. The undercoat layer 3 may be disposed so as to be in contact with the substrate 2, or another layer may be provided between the undercoat layer 3 and the substrate 2.

[0019] It is preferable that a resin component is contained in the undercoat layer 3. The resin component used in the undercoat layer 3 is not particularly limited, but at least one selected from the group consisting of natural rubber, synthetic rubber, urethane resin, acrylic resin, ester resin, and epoxy resin can be used.

[0020] The natural rubber used in the undercoat layer 3 is obtained by purifying latex that flows out when the bark of Hevea brasiliensis is cut, and then coagulating and drying it, and mainly contains cis-1,4-polyisoprene. The natural rubber may be a graft polymer obtained by graft copolymerization of natural rubber with monomers such as (meth)acrylic acid, styrene, and acrylonitrile. From the viewpoint of adhesiveness of the adhesive tape 1, it is preferable to use a graft polymer obtained by graft copolymerization of natural rubber with methyl methacrylate (MMA).

[0021] The synthetic rubber used in the undercoat layer 3 is not particularly limited, and at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene copolymer rubber (SBR), acrylonitrile-butadiene copolymer rubber (NBR), chloroprene rubber (CR), butyl rubber (IIR), ethylene-propylene rubber (EPM), and ethylene-propylene-diene rubber (EPDM) can be used. The synthetic rubber may be a graft polymer obtained by graft copolymerization of a synthetic rubber with a monomer such as (meth)acrylic acid, styrene, or acrylonitrile. From the viewpoint of adhesiveness of the adhesive tape 1, it is preferable to use a graft polymer obtained by graft copolymerization of a styrene-butadiene copolymer rubber (SBR) and methyl methacrylate (MMA).

[0022] There are no particular limitations on the urethane resin used in the undercoat layer 3, so long as it is a polymer having a urethane bond. The urethane resin can be obtained by a polyaddition reaction between a polyisocyanate and a polyol.

[0023] As the polyisocyanate, for example, at least one selected from the group consisting of tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), xylylene diisocyanate (XDI), hydrogenated xylylene diisocyanate (H6XDI), naphthalene diisocyanate (NDI), norbornene diisocyanate (NBDI) and hydrogenated diphenylmethane diisocyanate (H12MDI) can be used.

[0024] As the polyol, for example, at least one of polyether polyol and polyester polyol can be used. As the polyether polyol, for example, at least one selected from the group consisting of polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol can be used. As the polyester polyol, for example, at least one selected from the group consisting of polyethylene adipate, polybutylene adipate, polyhexene adipate, polyethylene oxalate, polybutylene oxalate, polyhexene oxalate, polyethylene succinate, polybutylene succinate, and polyhexene succinate can be used.

[0025] The acrylic resin used in the undercoat layer 3 is the same as that usable in the adhesive layer 4 described below.

[0026] The thickness of the undercoat layer 3 is not particularly limited, but is preferably from 0.3 μm to 2.0 μm, and more preferably from 0.3 μm to 1.0 μm. By setting the thickness of the undercoat layer 3 within this range, it is possible to obtain an adhesive tape 1 with good adhesive strength.

[0027] [Adhesive layer] The adhesive layer 4 is disposed on the surface of the undercoat layer 3 opposite to the substrate 2. The adhesive layer 4 may be disposed so as to be in contact with the surface of the undercoat layer 3, or another layer may be provided between the adhesive layer 4 and the undercoat layer 3.

[0028] The adhesive layer 4 contains an acrylic resin. The acrylic resin is a polymer obtained by polymerizing, but not limited to, an acrylic acid or (meth)acrylic acid ester monomer. In this specification, (meth)acrylic acid ester means an acrylic acid ester or a methacrylic acid ester. In the (meth)acrylic acid ester, examples of the alcohol that constitutes the (meth)acrylic acid ester by dehydration condensation include aliphatic alcohols having 1 to 30 carbon atoms. In addition, examples of the alcohol that constitutes the (meth)acrylic acid ester by dehydration condensation include aliphatic alcohols having 2 to 20 carbon atoms. In addition, these alcohols may be used alone or in combination of two or more.

[0029] As the (meth)acrylic acid ester, for example, at least one selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isobornyl (meth)acrylate, glycidyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, and eicosyl (meth)acrylate can be used.

[0030] The acrylic resin may be an emulsion-based acrylic resin. In particular, an aqueous emulsion-based acrylic resin is obtained by emulsion polymerization of a monomer such as a (meth)acrylic acid ester in water, and does not need to be dissolved in an organic solvent, so it is preferable from the viewpoint of volatile organic compounds (VOC) countermeasures.

[0031] The acrylic resin may be a copolymer of a monomer such as a (meth)acrylic acid ester monomer and another monomer. As the other monomer, for example, at least one selected from the group consisting of ethylene, propylene, styrene, vinyl chloride, vinylidene chloride, vinyl acetate, methyl methacrylate, acrylonitrile, and acrylamide can be used. In addition, the acrylic resin may be a copolymer with a monomer that forms a tackifier resin described later.

[0032] The resin component that can be used in the adhesive layer 4 is not particularly limited as long as it contains an acrylic resin, but may further contain at least one selected from the group consisting of urethane resin, ester resin, epoxy resin, natural rubber, synthetic rubber, tackifier resin, softener, and antioxidant. In order to improve the adhesive strength of the adhesive layer 4, it is preferable to use natural rubber and a tackifier resin. Also, in order to improve the flexibility of the adhesive layer 4, it is preferable to use a softener. Furthermore, in order to prevent deterioration of the adhesive component of the adhesive layer 4, it is preferable to use an antioxidant.

[0033] The natural rubber that can be used in the adhesive layer 4 is the same as that that can be used in the undercoat layer 3 .

[0034] There are no particular limitations on the tackifier resin that can be used in the adhesive layer 4, and it is possible to use one that improves the adhesive strength of the adhesive layer 4. As the tackifier resin, for example, at least one selected from the group consisting of rosin ester, terpene phenol, rosin-based resin, terpene-based resin, aromatic hydrogenated resin, aliphatic hydrogenated resin, coumarone-indene-based resin, phenol-based resin, and styrene-based resin can be used.

[0035] The softener that can be used in the adhesive layer 4 is not particularly limited, and any softener that improves the flexibility of the adhesive layer 4 can be used. Examples of the softener include styrene-based resins and petroleum-based softeners, and these can be used alone or in appropriate combination.

[0036] The antioxidant that can be used in the adhesive layer 4 is not particularly limited, and can be one that prevents deterioration of the adhesive component of the adhesive layer 4. As the antioxidant, for example, at least one selected from the group consisting of a phenol-based antioxidant, an amine-based antioxidant, a phosphorus-based antioxidant, a sulfur-based antioxidant, and a hydrazine-based antioxidant can be used.

[0037] The adhesive layer 4 preferably contains 40% by mass or more of acrylic resin. By containing 40% by mass or more of acrylic resin, discoloration of the adhesive tape 1 can be suppressed even at high temperatures such as in an engine room. From the viewpoint of adhesiveness, the adhesive layer 4 preferably contains 0% by mass or more and 20% by mass or less of natural rubber and 40% by mass or more and 70% by mass or less of acrylic resin. Furthermore, the adhesive layer 4 more preferably contains 0% by mass or more and 10% by mass or less of natural rubber, 40% by mass or more and 65% by mass or less of acrylic resin, and 10% by mass or more and 25% by mass or less of tackifier resin.

[0038] The thickness of the adhesive layer 4 is from 5 μm to 20 μm, and preferably from 8 μm to 15 μm. By setting the thickness of the adhesive layer 4 in this range, an adhesive tape 1 with good adhesive strength can be obtained.

[0039] As described above, the substrate 2 can be formed by T-die processing, and there is no need to add a lubricant. Therefore, there is no decrease in adhesive strength due to the lubricant blooming on the surface of the substrate 2, and the thickness of the adhesive layer 4 can be kept within the above range. Therefore, the adhesive tape 1 is less likely to cause the telescope phenomenon or stickiness on the side of the tape.

[0040] [Adhesive tape] The adhesive tape 1 of this embodiment comprises a substrate 2 containing an olefin resin, an undercoat layer 3 disposed on one side of the substrate 2, and an adhesive layer 4 disposed on the side of the undercoat layer 3 opposite the substrate 2.

[0041] The thickness of the adhesive tape 1 is not particularly limited, but is preferably 35 μm to 240 μm, and more preferably 60 μm to 130 μm. By making the thickness of the adhesive tape 1 35 μm or more, an adhesive tape 1 having good tensile strength can be obtained. Furthermore, by making the thickness of the adhesive tape 1 240 μm or less, it is possible to suppress the occurrence of wrinkles that occur when the adhesive tape 1 is wrapped around an electric wire or the like.

[0042] The adhesive strength of the adhesive tape 1 on its back surface is from 1.0 N / 10 mm to 3.0 N / 10 mm, and preferably from 1.5 N / 10 mm to 2.4 N / 10 mm. The adhesive strength on its back surface means the adhesive strength of the adhesive tape 1 on the back surface of the adhesive tape 1, i.e., the surface of the substrate 2 opposite to the adhesive layer 4. By setting the adhesive strength on its back surface in this range, an adhesive tape 1 that is difficult to peel off when laminated and has good adhesive strength can be obtained. The adhesive strength on its back surface can be measured in accordance with Japanese Industrial Standard JIS Z 0237 (Testing method for adhesive tapes and adhesive sheets).

[0043] The pressure-sensitive adhesive tape 1 can be used, for example, for covering electric wires, bundling electric wires in a wire harness, and protecting electric wires and wire harnesses.

[0044] Thus, the adhesive tape 1 of this embodiment comprises a substrate 2 containing an olefin resin, an undercoat layer 3 disposed on one side of the substrate 2, and an adhesive layer 4 containing an acrylic resin and having a thickness of 5 μm to 20 μm disposed on the side of the undercoat layer 3 opposite the substrate 2, and has an adhesive strength to its own back surface of 1.0 N / 10 mm to 3.0 N / 10 mm. Therefore, it is possible to provide an adhesive tape 1 that suppresses the occurrence of the telescope phenomenon and stickiness on the side of the tape and has excellent adhesive strength.

[0045] [Wire harness] The wire harness according to the present embodiment includes the above-mentioned adhesive tape 1. The above-mentioned adhesive tape 1 is excellent in the effect of suppressing the occurrence of the telescope phenomenon and stickiness on the side surface of the tape. Therefore, by wrapping such an adhesive tape around electric wires and bundling them, it can be preferably used as a wire harness for an automobile, for example. That is, the wire harness preferably includes the above-mentioned adhesive tape. EXAMPLES

[0046] The present embodiment will be described in more detail below with reference to examples and comparative examples, but the present embodiment is not limited to these examples.

[0047] [Sample preparation for Examples and Comparative Examples] <Preparation of adhesive tape> The olefin resin, antioxidant, and talc were blended and melt-kneaded at 200°C using a twin-screw kneading extruder, and the extruded strand was water-cooled and passed through a pelletizer to obtain pellets. In Comparative Example 1, a lubricant was also blended in addition to the olefin resin, antioxidant, and talc to produce pellets.

[0048] The talc-containing olefin resin pellets were used in a T-die film molding machine to prepare a substrate having a thickness of 90 μm at a temperature of 200 ° C. Next, a solution was prepared by diluting the material of the undercoat layer with water so that the non-volatile content was 30% by mass. This solution was applied to the substrate with a bar coater so that the film thickness after drying was 0.5 μm, and dried in a 100 ° C environment for 3 minutes to prepare an undercoat layer. Furthermore, a solution was prepared by diluting the material of the adhesive layer with water so that the non-volatile content was 55% by mass. This solution was applied on the dried undercoat layer with a bar coater so that the film thickness after drying was the thickness shown in Table 1, and dried in a 100 ° C environment for 3 minutes to prepare an adhesive layer. The obtained sheet of adhesive tape was wound around a core to prepare a roll of adhesive tape. The roll was cut to a width of 19 mm and evaluated. The components used are as follows.

[0049] (base material) Olefin resin: Prime TPO (registered trademark) R110E, manufactured by Prime Polymer Co., Ltd. Antioxidant: IRGANOX® 1010, manufactured by BASF Japan Ltd. Talc: MicroAce (registered trademark) P-8, manufactured by Nippon Talc Co., Ltd. Lubricant (Comparative Example 1): CYANOX (registered trademark) 1212, manufactured by SOLVAY

[0050] (Undercoat layer) Graft copolymer of natural rubber and methyl methacrylate: MG-25, manufactured by Resitex Co., Ltd.

[0051] (Adhesive layer) Acrylic resin (emulsion acrylic resin): SC-2, manufactured by Musashino Chemical Co., Ltd. Natural rubber: HA latex, manufactured by Resitex Co., Ltd. Tackifier resin: E-726, manufactured by Arakawa Chemical Industries, Ltd. Softener: Arakawa Chemical Industries, Ltd., KE-799 Antioxidant: Arakawa Chemical Industries, Ltd., KE-800

[0052] [evaluation] <Self-back adhesive strength> According to JIS Z 0237, a sample with a width of 19 mm and a length of 250 mm was cut out, glued and pressed to the back of the sample, folded back the remaining portion at 180°, and left for 30 minutes. After that, the sample was peeled off at 180° at a speed of 300 mm / min using a tensile tester, and the tensile load value at this time was converted to a 10 mm width to calculate the adhesive strength (N / 10 mm). The measured value was the average value of the results for 5 samples.

[0053] <Telescope> If the difference between the height of the wrapped tape after heating at 80°C for 2 hours and the height of the wrapped tape before heating was less than 1.0 mm, it was evaluated as "◎" (pass); if it was 1.0 mm or more and 2.0 mm or less, it was evaluated as "○" (pass); and if it exceeded 2.0 mm, it was evaluated as "×" (fail).

[0054] <Side stickiness> Glass beads with a diameter of about 2 mm are spread out, the tape is placed side down on top of it, and a weight of 200 g is placed on top of it. After leaving it for 10 minutes, the weight of the tape attached to the tape is measured and divided by the area of ​​the tape (g / cm 2 ) was measured. 2 If it is less than 0.04g / cm, it is marked as "◎" (passing). 2 More than 0.05g / cm 2 The following cases are marked as "○" (passed): 0.05 g / cm 2 When the test result exceeded the limit, the test result was evaluated as "×" (failure).

[0055] <Tape edge peeling> After wrapping the tape around a bundle of wires focused to an outer diameter of 10 mm, the wires were left at 50°C for one week. The length of the peeled portion at the end of the tape was then checked. The length of the peeled portion was evaluated as "◎" (pass) if it was less than 1.0 mm, "○" (pass) if it was 1.0 to 2.0 mm, and "×" (fail) if it was more than 2.0 mm.

[0056] [Evaluation Results] The results of the evaluation using the above-mentioned evaluation methods are shown in Table 1.

[0057] [Table 1]

[0058] As shown in Table 1, the adhesive tapes of Examples 1 to 4 did not use a lubricant in the substrate, had an adhesive layer thickness of 5 μm or more and 20 μm or less, and had a self-backside adhesive strength of 1.0 N / 10 mm or more and 3.0 N / 10 mm or less. The adhesive tapes of Examples 1 to 4 also passed the evaluation results of telescoping, side stickiness, and tape end peeling, which were "◎" or "○". Thus, the adhesive tapes of Examples 1 to 4 suppressed the occurrence of the telescoping phenomenon and stickiness on the tape side, were less likely to peel off at the tape end, and had excellent adhesive strength.

[0059] On the other hand, the adhesive tape of Comparative Example 1 used a lubricant in the substrate and the thickness of the adhesive layer exceeded 20 μm, so the evaluation results for telescoping and side stickiness were "x", and it failed. The adhesive tape of Comparative Example 2 did not use a lubricant in the substrate, but the thickness of the adhesive layer exceeded 20 μm and the adhesive strength on the back side exceeded 3.0 N / 10 mm, so the evaluation results for telescoping and side stickiness were "x", and it failed. Furthermore, the adhesive tape of Comparative Example 3 did not use a lubricant in the substrate, but the thickness of the adhesive layer was less than 5 μm and the adhesive strength on the back side was less than 1.0 N / 10 mm, so the evaluation result for tape end peeling was "x", and it failed.

[0060] Although the present invention has been described above with reference to the examples, the present invention is not limited to these examples, and various modifications are possible within the scope of the present invention. [Explanation of symbols]

[0061] 1 adhesive tape 2 Base material 3 Undercoat layer 4 Adhesive layer

Claims

1. A substrate containing an olefin resin; An undercoat layer disposed on one surface of the substrate; an adhesive layer that is disposed on the surface of the undercoat layer opposite to the substrate, contains an acrylic resin, and has a thickness of 5 μm or more and 20 μm or less; The adhesive tape has a backside adhesive strength of 1.0 N / 10 mm or more and 3.0 N / 10 mm or less.

2. The pressure-sensitive adhesive tape according to claim 1 , wherein the undercoat layer contains a graft polymer obtained by graft copolymerization of natural rubber and methyl methacrylate.

3. The adhesive tape according to claim 1 , wherein the adhesive layer further contains natural rubber.

4. A wire harness comprising the pressure-sensitive adhesive tape according to claim 1 or 2.

Citation Information

Patent Citations

  • Adhesive tape

    JP2002105411A

  • Halogen-free adhesive tape

    JP2006161008A

  • Adhesive tape

    JP2014240484A

  • Self-adhesive tape

    JP2013194061A